Unexpected judgments: the role of gender identity and provocation on blame and affect in a mock jury paradigm - Totton, Rebecca R.; McKeon, Kayla (Frontiers in Social Psychology, 2024)
Panic defenses are a form of legal defense positing that a defendant is less culpable for their crime because of an extreme emotional reaction. In two Studies (Total N = 995) previously existing scales and vignettes were used to evaluate perceptions of panic defenses when the victim was a transgender woman, transgender man, or a gay man. Study 1 (N = 557) used a 2 (sexual provocation or non-sexual provocation) x 3 (transgender woman, transgender man, or gay man victim) design to evaluate perceptions of victim blame, negative affect, and perception that the crime was a hate crime. Contrary to demographic data trends, Study 1 found that transgender women were rated more positively as victims, were blamed less than transgender men or gay men, and that the crime was more likely to be labeled as a hate crime. Study 2 (N = 438) was a replication of Study 1. While the results were largely non-significant, the trend in means was in the same direction as the findings of Study 1. We argue that these findings, despite not being in line with broader data on the topic, are important evidence that anti-transgender research, particularly in mock jury settings, may need to reimagine existing designs and vignettes to understand rates of violence and discrimination toward transgender communities.